Carryover of tembotrione and atrazine affects yield and quality of potato tubers - Reis, Marcelo Rodrigues; Aquino, Leonardo Angelo; Diniz Melo, Christiane Augusta; Silva, Daniel Valadao; Dias, Roque Carvalho [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2018)
Crop rotation improves potato (Solanum tuberosum L.) crops; however, in some cases, it can have some negative effects due to the herbicides previously used in crops under rotation. These effects are the decline in the yield and the appearance of physiological disorders, including cracked tubers, which impair the quality and economic value of the potato. Two field experiments were performed with applications of tembotrione and atrazine, alone or in combination. In the Rio Paranaiba (Minas Gerais State) area, in clay soil, the herbicides were applied at post-emergence in corn (Zea mays L.). After corn harvest and soil preparation, the potatoes were planted. In the Serra do Salitre (Minas Gerais State) area, in the medium texture soil, the herbicides were applied and incorporated into the soil, and the potatoes were planted the day after. No injuries were found in the shoots. Decline in the potato yield was found only in the medium texture soil (Serra do Salitre). Atrazine did not affect the quality of potato tubers. In the two areas, tembotrione promoted cracks in Atlantic potato tubers.
Keywords: Atlantic; herbicide; physiological disorder; Solanum tuberosum